Impact of Ethnic Diversity in Leadership, Board Size, Foreign Ownership, and Leverage on Financial Performance: The Moderating Role of the President Commissioner’s Ethnicity - Mansyurah, Mardiani (Indonesian Management and Accounting Research, 2022)
The purpose of this study was to examine the influence of the ethnicity of the president director, the size of the board of commissioners, foreign ownership, and leverage on the company's financial performance, which is moderated by the ethnicity of the president commissioner. The research sample is companies with market capitalization values above Rp 5 trillion listed on the Indonesia Stock Exchange from 2015-2018. The number of samples used was 96 companies selected using purposive sampling. Based on the analysis results, the ethnicity of the president-director positively affects the company's financial performance. At the same time, the size of the board of commissioners and foreign ownership do not affect the company's financial performance. Leverage does not affect the company's financial performance. This study also shows that the ethnicity of the president commissioner does not strengthen the positive influence of the ethnicity of the president director, the size of the board of commissioners, foreign ownership, and financial performance. The ethnicity of the president commissioner also does not weaken the negative influence of leverage on the company's financial performance.